A colorimetric and ratiometric fluorescent probe with Meldrum's acid as the recognition group for in vitro and in vivo imaging of hypochlorite. (April 2020) - Yang, Lili; Ruan, Songsong; Zhang, Anqi; Hu, Mengyan; Zhang, Jie; Sheng, Kangjia; Tian, Jing; Zhang, Yongmin; Wu, Shaoping; Li, Jianli
Abstract: The detection of ClO − is vital to comprehend the accurate effect of ClO − in various diseases and therapeutic interventions by fluorescent probe method. Herein, a special ratiometric probe DDD was designed and efficiently synthesized via a simple process for hypochlorite detection. The selectivity and sensitivity of probe DDD was excellent and the detection was not influenced by other reactive oxygen species. Probe DDD exhibited a fast response (<1 s), wide Stokes Shift (>100 nm), sensitive limit of detection (78 nM) and two well-separated emission (555 nm and 635 nm). The emission intensities ratio (I555 /I635 ) was linearly enhanced (I555 /I635  = 0.6273X - 1.9313) with the ClO − concentration range from 4.0 to 20.0 μM. Furthermore, probe DDD has been successfully evaluated in monitoring exogenous HClO in SH-SY5Y neuroblastoma cells and zebrafish larvae with low cytotoxicity, good cell permeability and biocompatibility. Graphical abstract: Image 1 Highlights: A novel ratiometric fluorescent probe was designed and synthesized for detecting HClO. Probe DDD exhibits a short response time, a low detection limit and large Stokes shift. Probe DDD was successfully performed well in monitoring exogenous HClO in living cells and zebrafish larvae.